2020
DOI: 10.1177/0971523120947088
|View full text |Cite
|
Sign up to set email alerts
|

Gender Variant Children and Institutional Arrangements: Exploring the Phenomenon from South Asian Perspective

Abstract: This paper explores and assesses the presence/absence of institutional arrangements in educational settings for addressing the concerns of gender-variant children (GVC) through a sample survey of schools in the three-country context of India, Sri Lanka and Nepal. This research highlights the need for effective regulatory, normative and cognitive structures to address issues of childhood gender variance. With a contextual analysis of recent developments and comprehensive study of data reports in the three count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Similarly, the restrictions of gender nonconformity in adolescence that coincided with the onset of puberty particularly in the case of boys, have been documented previously (Spivey-Rita et al, 2018;Renade, 2018;Kuru Uthumpala, 2013). Furthermore, the experiences related to peers and teachers in school which were recalled by the men and women in this inquiry also mirrored previous studies of pervasive harassment and victimization reported by gender nonconforming adolescents who challenged stereotypical renditions of masculinity and femininity in school (Timmins et al, 2020;Tiwari, 2020;Baams, 2018;).…”
Section: Reactions Of Adults and Peers To Participants' Gnc From Chil...supporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, the restrictions of gender nonconformity in adolescence that coincided with the onset of puberty particularly in the case of boys, have been documented previously (Spivey-Rita et al, 2018;Renade, 2018;Kuru Uthumpala, 2013). Furthermore, the experiences related to peers and teachers in school which were recalled by the men and women in this inquiry also mirrored previous studies of pervasive harassment and victimization reported by gender nonconforming adolescents who challenged stereotypical renditions of masculinity and femininity in school (Timmins et al, 2020;Tiwari, 2020;Baams, 2018;).…”
Section: Reactions Of Adults and Peers To Participants' Gnc From Chil...supporting
confidence: 78%
“…Furthermore, gay adolescent boys report more discrimination and violence than lesbian girls (Dunn & Szymanski, 2018). School settings in 88 Lesbian, Gay and Bisexual Adults' Recollections of Others' Reactions to Their Early Gender Non-Conformity Page 85-98 SJHS(2021) Vol( 2) Issue(1) the South Asian region, particularly in India, Sri Lanka, and Nepal appear to similarly be hostile towards students of non-normative sexual and gender presentations (Tiwari, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%